A QUALITATIVE STUDY OF RETAIL BUSINESS WARFARE - Irawan, Andri; Ibrahim, Muhdi B.Hi; Sutisna, Entis; Marihi, Laode (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2025)
The current situation has created a state of disequilibrium between modern and traditional retail, which has been further exacerbated by the disruption of information and communication technology. The disruption of information and communication technology has resulted in an imbalanced trade war between modern and traditional retail. The objective of this study is to ascertain the circumstances surrounding the emergence of the trade war and its subsequent impact on consumer shopping behaviour in Jayapurag City. This study employs a qualitative methodology, utilising primary data obtained through in-depth interviews with retail leaders and proprietors. This study focuses on modern and traditional retailers in Jayapura City. The findings indicate that the business conflict between modern and traditional retailers presents both challenges and opportunities for both groups. Nevertheless, the extant circumstances preclude collaboration between the two, yet the possibility of collaboration is evident should the government succeed in establishing business regulations for both.